The Effect of Product Quality, Service Quality and Digital Marketing on Consumer Satisfaction of Harrum Mart Retail Stores - Robi Santoso; Tri Endang Yulianti; Reni Diah Setiowati; Ilham Setio Wibowo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In an increasingly advanced era in terms of digital marketing encouraging people to adapt to increasingly advanced technology, in the digital era purchase decisions can be made based on several applications that are often used by the public, currently, Harrum Mart retail stores are stores that sell their merchandise online and offline, in its use the quality of the product can describe the extent of the product's ability to meet the needs of consumers, , when the service is in accordance with consumer expectations, it can be said to be effective in increasing consumer satisfaction. Quality service should be carried out continuously in accordance with the needs of consumers and the company's goals. Based on the results of the study, it shows that there is no direct positive influence of Product Quality on Digital Marketing, there is no positive influence of Service Quality on Digital Marketing, there is a positive influence of Digital Marketing on Consumer Satisfaction, there is a positive influence of Product Quality on Consumer Satisfaction, there is a positive influence of Service Quality on Consumer Satisfaction Keywords: , , ,